Bone mineral density in high-level endurance runners: part a-site-specific characteristics - Herbert, A. J.; Williams, A. G.; Lockey, S. J.; Erskine, R. M.; Sale, C.; Hennis, P. J.,; Day, S. H.; Stebbings, G. K. (European Journal of Applied Physiology, 2021)
Purpose Physical activity, particularly mechanical loading that results in high-peak force and is multi-directional in nature, increases bone mineral density (BMD). In athletes such as endurance runners, this association is more complex due to other factors such as low energy availability and menstrual dysfunction. Moreover, many studies of athletes have used small sample sizes and/or athletes of varying abilities, making it difficult to compare BMD phenotypes between studies.